Knowledge, Attitude, and Practice of Bee Venom Acupuncture Therapy Among Patients in West of Libya - Somaia Elsaedi; Amnnah Ahmed; Ahlam Mohamed; Ayat Omar; Shaima Aburas; Hajer Ali; Abdulrhman Akasha (AlQalam Journal of Medical and Applied Sciences, 2025)
Apitherapy is an alternate therapy that relies on the usage of honeybee products, most importantly bee venom for the treatment of many human diseases. Bee venom contains several active molecules such as peptides and enzymes that have advantageous potential in treating inflammation and central nervous system diseases. Moreover, bee venom has shown promising benefits against different types of cancer as well as anti-viral activity. This study explores the effects and perceptions of bee venom therapy (BVT) among a selected population in Libya. The research primarily focuses on the demographics of individuals undergoing BVT, the frequency and types of symptoms experienced post-therapy, and the various conditions for which BVT is utilized. A cross-sectional descriptive study of 100 participants using a structured questionnaire on knowledge, attitude scale, and practice was done at three regions in Libya including Tripoli, Gerian & Yefran during Jun and July 2024. A randomized sample size that included a diverse age group and both genders. The data were presented as frequencies and percentages. Excel is used to enter and analyze the data. Results indicated a broad acceptance of BVT, with a majority of participants reporting symptomatic relief for various conditions such as muscular pain, back pain, and nerve-related issues. However, a significant portion of participants also reported common side effects such as swelling and localized pain. The study highlights the necessity for more extensive research to validate the efficacy of BVT and to better understand the long-term impacts and potential risks associated with the therapy.